Risk factors for postoperative complications and long-term survival in lung cancer patients older than 80 years. (18th December 2017) - Hino, Haruaki; Karasaki, Takahiro; Yoshida, Yukihiro; Fukami, Takeshi; Sano, Atsushi; Tanaka, Makoto; Furuhata, Yoshiaki; Ichinose, Junji; Kawashima, Mitsuaki; Nakajima, Jun
Abstract: OBJECTIVES: The number of octogenarian lung cancer patients undergoing radical surgery has been increasing recently. However, knowledge regarding the risk factors for postoperative complications and reliable predictive factors for long-term survival is limited. This study aimed to investigate the risk factors of postoperative complications, and reliable prognostic factors, in lung cancer patients older than 80 years. METHODS: Lung cancer patients aged 80 years or older who underwent radical surgery were retrospectively studied; a multi-institutional analysis was conducted from January 1998 to December 2015. Preoperative and postoperative clinical data, including age, gender, smoking history, body mass index, respiratory function, Charlson Comorbidity Index, Glasgow Prognostic Score, surgical procedure, cancer histology, clinical and pathological stage, surgical result and survival time, were collected. RESULTS: A total of 337 patients, comprising 216 (64.1%) men and 121 (35.9%) women were enrolled. The median age was 82 (range 80–92) years. Of the 337 patients, 205 (60.8%) had preoperative comorbidities. Postoperative complications were observed in 119 (35.3%) patients; postoperative mortalities occurred in 6 (1.8%) patients. Univariate and multivariate analyses showed that male gender ( P  = 0.01) and operation time ( P  = 0.047) were associated with postoperative complications; in contrast, pathological Stage III ( P  < 0.001), male gender ( P  = 0.01), Charlson Comorbidity Index ≥2 ( P  = 0.03) and Glasgow Prognostic Score = 1/2 ( P  = 0.04) were independent prognostic factors for overall survival. CONCLUSIONS: The risk factors for postoperative complications (male gender and operation time) and the predictive factors affecting long-term survival (male gender, Charlson Comorbidity Index, Glasgow Prognostic Score and P-stage) should be taken into account for the effective management of patients older than 80 years with lung cancer, undergoing surgery.